Palatal root endodontic microsurgery in maxillary molars using the palatal approach: a case study - Cheng Bi; Shuchen Xu; Bin Peng; Pei Zheng (BMC, 2024)
Abstract Background In clinical practice, the buccal approach is typically the primary choice for endodontic microsurgery. Owing to the thickness of the buccal bone plate, the distance between the buccal bone plate and palatal lesion location, and soft tissue traction, the palatal approach may be more suitable for microsurgery for apical periodontitis of the palatal roots of the maxillary molars. However, the length of the palatal root, location of the greater palatine artery (GPA) and foramen (GPF), and surgical field of observation make palatal surgery challenging. Case presentation With the aid of Cone-beam computed tomography imaging, the palatal approach was successfully applied in nine cases of endodontic microsurgery of the palatal root of a maxillary molar with a periapical lesion in Hangzhou Stomatology Hospital from January to December 2022. Conclusions Complete healing was assessed based on clinical symptoms and radiographic images at the 3- and 24-month follow-up visits in all nine cases. Several tips have been proposed including surgical positioning, incision design, palate flap modification, bone removal, and root-end resection.